2021
DOI: 10.1186/s13063-021-05510-3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic potential of honey and Nigella sativa L. against hospital and community-based SARS-CoV-2 spread: a structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives Considering the therapeutic potential of honey and Nigella sativa (HNS) in coronavirus disease 2019 (COVID-19) patients, the objective of the study is defined to evaluate the prophylactic role of HNS. Trial design The study is a randomized, placebo-controlled, adaptive clinical trial with parallel group design, superiority framework with an allocation ratio of 1:1 among experimental (HNS) and placebo group. An interim analysis will be do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Most recently, Molnupiravir as early treatment has shown a reduced risk of hospitalization or death in at-risk, unvaccinated adults with Covid-19 ( Jayk Bernal et al, 2021 ). furthermore, Pfizer released phase 2/3 results from the PAXLOVID trial, confirming the novel COVID-19 oral antiviral treatment’s robust efficacy in reducing the risk of hospitalization or death by 89% (within 3 days of symptom onset) and 88% (within 5 days of symptom onset) compared to placebo; no deaths in non-hospitalized, high-risk adults with COVID-19 compared to placebo ( Archive, 2021 ), in addition, PAXLOVID has been authorized by the United States Food and Drug Administration ( Ashraf et al, 2021 ) as emergency use authorization and became the first oral antiviral authorized by FDA for treatment of COVID-19 ( U.S. Food and Drug Administration, 2021a ).…”
Section: Introductionmentioning
confidence: 79%
“…Most recently, Molnupiravir as early treatment has shown a reduced risk of hospitalization or death in at-risk, unvaccinated adults with Covid-19 ( Jayk Bernal et al, 2021 ). furthermore, Pfizer released phase 2/3 results from the PAXLOVID trial, confirming the novel COVID-19 oral antiviral treatment’s robust efficacy in reducing the risk of hospitalization or death by 89% (within 3 days of symptom onset) and 88% (within 5 days of symptom onset) compared to placebo; no deaths in non-hospitalized, high-risk adults with COVID-19 compared to placebo ( Archive, 2021 ), in addition, PAXLOVID has been authorized by the United States Food and Drug Administration ( Ashraf et al, 2021 ) as emergency use authorization and became the first oral antiviral authorized by FDA for treatment of COVID-19 ( U.S. Food and Drug Administration, 2021a ).…”
Section: Introductionmentioning
confidence: 79%
“…Patients were randomly assigned into one of the following four groups, 30 patients in each: Group (1) patients received a total oral dose of 900 mg Nigella sativa (Baraka ® , Pharco Pharmaceuticals, Cairo, Egypt) in the form of soft gelatin capsules containing 450 mg, given as two capsules twice daily for two weeks ( Mahdavi et al, 2015 ; Ashraf et al, 2021 ) in addition to the standard therapy. Group (2) patients received 2,000 IU of vitamin D3 (Davalindi ® , Medical Union Pharma, Cairo, Egypt) in the form of 1000-IU tablets given as two tablets, once daily, in addition to the standard therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Plants have a long history of being rich sources of active ingredients that are helpful against various kinds of disease, including viral infections. Accordingly, a recent study has shown that administration of Nigella sativa L. (black cumin) over 2 weeks reduces the severity of COVID-19 symptoms and elicited viral clearance [ 159 ]. The active compound in N. sativa seems to be thymoquinone, which shows high efficacy against SARS-CoV-2 according to recently published findings [ 160 , 161 ].…”
Section: Emerging Treatment Strategiesmentioning
confidence: 99%